Penanaman Karakter Sholeh Melalui Kegiatan Pembiasaan di RA Insan Madani Ngroto - Risyda Tahta Alfina; Permata Fitri Arfiani (Insititut Agama Islam Negeri (IAIN) Curup, 2022)
Character education in the Islamic perspective explains that the character or behavior of children can be formed and taught through the method of internalization. Teaching is done by building good values from within the child such as a good example from the teacher, good habituation, the existence of rules and motivations that are always accepted by children. The purpose of this research is to know repetition method that used in RA Insan Madani Ngoroto for developing the religious character. The research method that used was descriptive qualitative with purposive sampling. This research revealed that repetitive method that were used in RA Insan Madani are read qur’an, made 3 S (smile and greeting), developing communication with parents, doing weekly activity and developing courteous habits for kids.